Harmonising Psychological and Legal Perspectives on Teacher-Child Interactions: A Conceptual Framework for Early Childhood Education - Muhammad Noor Taufik Bin Abd Jalil Abd Jalil; Puput Mulyono; Aris Prio Agus Santoso; Ilham Komarudin (Journal of Early Childhood Education Research, 2025)
Purpose: Teacher-child interactions in early childhood education are often shaped by pedagogical practices that lack integration with child development psychology and legal frameworks for child protection. This study aims to develop a conceptual framework that integrates developmental psychology principles with legal regulations to guide quality teacher-child interactions in early childhood settings. Methodology: This qualitative study employs a library research approach, analysing secondary sources including academic literature on child development, early childhood pedagogy, and relevant legal frameworks governing child protection and early childhood education. Results : The analysis resulted in a conceptual framework comprising three core components: input (teacher knowledge of child development and legal standards), process (integration of developmentally appropriate pedagogy with child protection principles), and output (safe, rights-based, and quality interactions). The framework proposes implementation strategies through structured observation, reflective practice, professional supervision, and capacity-building training. Conclusions: The proposed conceptual framework offers a systematic approach to strengthening teacher-child interactions by bridging developmental psychology and legal regulations. While developed through library research, the framework requires empirical validation in early childhood education contexts. It provides a foundation for policy development and professional training programmes aimed at improving interaction quality while ensuring compliance with child protection standards.